1999
DOI: 10.1046/j.1469-0705.1999.14040256.x
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous multigate spectral Doppler imaging of the umbilical artery and placental vessels: novel ultrasound technology

Abstract: Simultaneous multigate spectral Doppler imaging provides simultaneous measurements of the velocity waveforms in the umbilical artery, chorionic and intraplacental vessels, and is a feasible and reproducible method of obtaining these data. The normal data presented may facilitate early detection of flow disturbances in the fetoplacental circulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Second, in all of these studies Doppler indices were obtained from the umbilical artery whereas in our study they were obtained from multiple locations in the arterial tree of the placenta, using SM-SDI. We believe this is a more sensitive method to detect alterations in the placental circulation 15 . Third, in the previous studies Doppler measurements were obtained before the beginning of exercise and after its conclusion, whereas in the present study all measurements were obtained during the exercise as well as before and after.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Second, in all of these studies Doppler indices were obtained from the umbilical artery whereas in our study they were obtained from multiple locations in the arterial tree of the placenta, using SM-SDI. We believe this is a more sensitive method to detect alterations in the placental circulation 15 . Third, in the previous studies Doppler measurements were obtained before the beginning of exercise and after its conclusion, whereas in the present study all measurements were obtained during the exercise as well as before and after.…”
Section: Discussionmentioning
confidence: 98%
“…The method of data collection has been described previously 7,15 but is summarized briefly as follows: the operator first selects a region of interest, using the conventional color Doppler image. The spectral Doppler scanning mode is activated.…”
Section: Methodsmentioning
confidence: 99%
“…Preeclampsia was defined as systolic blood pressure R140 mm Hg or diastolic blood pressure R90 mm Hg on at least two occasions, and when proteinuria of R300 mg per day was found. Blood flow resistance was measured in the left and right uterine, placental, and umbilical arteries at 24 and at 31 to 33 weeks of gestation by multigate Doppler ultrasonography (15). The test results for common hereditary or acquired thrombophilias in the present study were extracted from the data of our previous study (14).…”
Section: Materials and Methods Patients Definitions And Testsmentioning
confidence: 99%
“…Preliminary studies on the assessment of the intraplacental Doppler pulsatile indices (PI) during the second and third trimesters have been encouraging [15][16][17]. We have previously shown that the new Doppler method is reliable and can be used for the assessment of the fetoplacental circulation [1].The efficacy of this method in the prediction of adverse pregnancy outcome related to placental pathology has been described previously [17][18][19]. However, the clinical usefulness of the distribution curves of the Doppler indices and the intraplacental Doppler velocimetry indices obtained by the SDIM remain unclear.…”
Section: Introductionmentioning
confidence: 93%